CONSTRUCTIVISM FROM PHILOSOPHY TO MATHEMATICS LEARNING - Jaka Wijaya Kusuma; Rochmad Rochmad; Isnarto Isnarto; Hamidah Hamidah (International Journal of Economy, Education and Entrepreneurship, 2021)
Constructivism, especially philosophy, understands that knowledge is the result of construction in a personal human being.  Develop knowledge through social interaction with other human beings,   phenomena,  experiences, and environments.  Knowledge is considered correct if  it  has  significance  for    troubleshooting. Learning  in  a constructionist  view  offers  to  develop  concepts  and  perceptions  of  the  student  itself.   In the classroom process, teachers  take on  the role  of  moderators and  facilitators. A constructivist  teacher must understand the characteristics of a student's  mistakes    because the increase in  knowledge  is  through  mistakes  and  mistakes. Teachers  should  see  mistakes  as a source of  information about the    student's scheme of characteristics  and   thinking.  There are  four principles of  constructivism  in  mathematical learning.  First,the  psychological structure  must be before the occupation of the amount. Second, the structure of   background  knowledge  (schemata)  must be  developed  before  teaching  formal mathematics symbols. Third,  students  should have the  opportunity  to  find  and  form  their mathematical  relationships,   not  to  expose adult thinking.  Fourth,teachers  should  create an  atmosphere  of thinking  in the    classroom